Protocol for a randomised trial evaluating the comparative effectiveness of strategies to promote shared decision making for hip and knee osteoarthritis (DECIDE-OA study). Issue 2 (24th February 2019) - Mangla, Mahima; Bedair, Hany; Chang, Yuchiao; Daggett, Susannah; Dwyer, Maureen K; Freiberg, Andrew A; Mwangi, Sheila; Talmo, Carl; Vo, Ha; Sepucha, Karen
Abstract : Introduction: There are several different interventions available to promote shared decision making (SDM); however, little is known about the comparative effectiveness of different approaches. Objective: To examine the impact of patient-directed and physician-directed decision support strategies on the quality of treatment decisions for hip and knee osteoarthritis (OA). Trial design: A 2×2 factorial randomised controlled trial. Setting: One academic medical centre, one community hospital and one orthopaedic specialty hospital. Participants and interventions: The enrolment targets were 8 surgeons and 1120 patients diagnosed with hip or knee OA. Patients were randomly assigned to receive one of two different decision aids (DAs) stratified by site. The DAs varied in length, content and the level of detail regarding treatment options. Both DAs were available by paper or online. Surgeons were randomly assigned to receive a report detailing patients' goals and treatment preferences at the time of the visit or not. Eligible patients received their assigned DA before their visit and completed three surveys: before the visit (timepoint (T)1), 1-week postvisit (T2) and 6 months from either the visit date or surgery date for patients who underwent surgery (T3). Study staff and participating surgeons were not blinded, but the statistician conducting the analyses was blinded to the arms. Main outcome measure and analysis: The primary study outcome was decision quality, the percentage of patients who were well informed and received their preferred treatment. Secondary outcomes included involvement in decision making, surgical rates, health outcomes, decision regret and satisfaction. A logistic regression model with the generalised estimating equations approach was used to compare rates of decision quality between the groups and account for the clustering of patients within providers. Ethics and dissemination: Ethics approval was obtained through the institutional review board at the main site. The findings will be published in peer-reviewed journals. Trial registration number: NCT02729831; Pre-results .